DETERMINATION OF MELOXICAM IN TABLETS BY THIRD DERIVATIVE UV SPECTROPHOTOMETRIC METHOD - Zeynep Aydoğmuş; Faruk Alim (Sabiad)
Objectives: Meloxicam (MEL) is a selective cyclooxygenase inhibitor of enolic acid class drugs with analgesic and antipyretic effects. In this study, an easy, selective, fast, and sensitive third-order derivative spectrophotometric method was developed and validated for the determination of MEL in tablet formulation.Material and Methods: The absorption of MEL in a solution of methanol and 1 M sodium hydroxide (1:1, v/v) mixture was measured using the peak-to-zero method. This solution was found to be the most suitable for determining the drug by third-order derivative spectrometry. The wavelength at which the maximum absorption was achieved in the measurements was 341nm. The developed method has been validated in accordance with the International Conference on Harmonization guidelines (ICH).Results: The linear working range was 1.0 - 14.0 µg/mL. The limit of detection (LOD) and limit of quantification (LOQ) values were 0.22 and 0.75 μg/mL, respectively. The method was validated for linearity, accuracy, precision, recovery, and stability. The developed method was performed for the quantification of MEL in tablets, and the recovery percentage was found to be between 97.50% and 98.12%.Conclusion: The results show that the method is easy, simple, inexpensive, and fast compared to other published methods, in addition to being accurate and sensitive. The proposed method can be used as a very convenient alternative for the determination of MEL in pharmaceutical formulations in routine analysis in quality control.